Factors Influencing Adolescent Pregnancy at Morodadi Community Health Center - Titin Baso; Retno Dewi Prisusanti (Detector: Jurnal Inovasi Riset Ilmu Kesehatan, 2025)
Adolescent pregnancy remains a significant public health issue due to its association with adverse maternal, neonatal, and social outcomes. Various individual, familial, and social factors contribute to the occurrence of early pregnancy among adolescents. This study aimed to analyze the factors influencing adolescent pregnancy in the working area of Morodadi Community Health Center. This research employed a quantitative analytic observational design using a cross-sectional approach. The study involved 30 adolescent girls aged 15–19 years selected through purposive sampling. Data were collected using a structured and validated questionnaire assessing reproductive health knowledge, family support, peer influence, educational background, and exposure to reproductive health information. Statistical analysis was conducted using SPSS software, including univariate analysis to describe respondent characteristics and bivariate analysis using the Chi-square test to examine relationships between variables, with a significance level set at p < 0.05.The results indicated that reproductive health knowledge, family support, and peer influence were significantly associated with adolescent pregnancy (p < 0.05). Adolescents with limited reproductive health knowledge, inadequate parental supervision, and strong exposure to high-risk peer groups were more likely to experience early pregnancy. Conversely, adolescents who reported supportive family environments and positive peer interactions demonstrated a lower risk of pregnancy. In conclusion, adolescent pregnancy at Morodadi Community Health Center is influenced by a complex interaction of individual knowledge, family dynamics, and social environment. Strengthening comprehensive reproductive health education, enhancing parental involvement, and promoting positive peer support systems are essential strategies for preventing adolescent pregnancy. Community health centers play a crucial role in implementing adolescent-friendly health services to support healthier reproductive outcomes.